Kegiatan Ekstrakurikuler Musik di SMA PGRI 2 Padang - Riko Saputra; Tulus Handra Kadir; Yos Sudarman (FBS Universitas Negeri Padang, 2014)
Abstract This research was aimed at describing the extracurricular activities of music at SMA PGRI 2 Padang. This was descriptive research whuch used qualitative approach. The result of the research indicated that the extracurricular activities of music were designed based on the goals to be achieved. Encouranging the students to be creative and have skills in music by teaching the basic technique of playing music were the preliminary efforts done by the teacher. In this phase the teacher also trained the students to play particular music individually. The activities started from teaching the students to play rhythm guitar. Melodic guitar, bass, drum, vocal and the basic technique of playing traditional music instuments such as talempong, gendang tambua and sarunai. Kata kunci : Kegiatan, Ekstrakurikuler, Musik